In vitro gas production and dry matter degradability of cassava top and maize stover mixture ensiled with albizia saman pods (2017)
In vitro gas production is an indication of microbial degradability of feed samples. Thus, varying levels of mixture of cassava top (CT) and maize stover (MS) ensiled with Albizia saman pods (ASP) were examined. The feedstuff were dried and milled for gas determination in a completely randomized design. Samples were incubated using in vitro gas production technique. Gas production was measured at 3, 6, 9, 12. 15, 18, 21 and 24 h post incubation to estimate total gas volume (TGV), methane (CHJ, metabolisable energy (ME; M.J/Kg DM), organic matter digestibility (OMD; %) and short chain fatty acids (SCFA; pmol/200 mg DM), dry matter (DM, %) increased significantly (p<0.05) as inclusion of Albizia saman pods increases across the treatments. The crude protein (CP. %) contents were similar across the treatments. The total gas volume (TGVmL) produced by the diets were similar across the treatments. The values ranged from 4.81 to 5.26 for ME, 35.16 to 36.32for OMD, 0.13 to 0.21 for SCFA and 5.33 to 7.33 for CH, production with no significant difference. The result showed that in vitro fermentation of the mixture of cassava top and maize stover ensiled with Albizia saman pods at 0:40:60% increased the dry matter degradability by 15%, enhanced metabolisable energy, organic matter digestibility and short chain fatty acids.